Occupational Stress among School Teachers Working in Kathmandu, Nepal - Joshi, Padma Raj (AJOIS: Academic Journal of Interdisciplinary Studies, 2024)
The purpose of this study was to explore the effect of occupational stress among male and female school teachers working in Kathmandu, Nepal. The study was conducted on 210 male (105) and female (105) teachers were chosen as convenient sampling method. For this study, the occupational stress index (OSI) developed by Srivastava and Singh, 1981 was used. A Pearson correlation coefficient was computed between age and occupational stress which was statistically insignificant, R = .001, N=210, p=0.988. A Chi-Square test between gender and occupational stress was significant, χ2 (2, N=210) = 28.007. T-test was conducted to compare occupational stress for males and females. There was a significant difference in the scores for male (M=132.81, SD=17.504) and female (M=145.72, SD=21.708); t (199.056) =-4.745.